Effects of Ficus deltoidea leaf extracts on rat Uterine Tissue Contractility and Proteome / Khaniza Hasliza Abdul Khalil - Khaniza Hasliza , Abdul Khalil (2019)
Ficus deltoidea, a plant known for its uterotonic effect, is a herb used by women to improve their wellbeing. The aim of this study was to investigate the molecular mechanisms underlying the uterotonic property of crude extract (CE) and water fractionated (WF) leaf extracts of F. deltoidea. Female nulliparous ICR mice and WKY rats were administered with CE and WF, with the former animals subjected to an embryo implantation study. All animals were measured for their levels of steroid hormones, whilst resected uterine segments of the WKY rats were subjected to a contractility study and analyzed for the expression of the M2 muscarinic acetylcholine receptor (mAChR). The embryo implantation study demonstrated failure of conception of mice administered with WF at 100 mg/kg body weight although the animals did not show any signs of toxicity. Isolated uterine segments of WKY rats administered with the same dose of CE and WF demonstrated increased contractility, which appeared to be associated with higher levels of serum progesterone and uterine tissue expression of M2 mAChR. F. deltoidea has the ability to increase uterine contractility by alteration of serum progesterone and uterine tissue M2 mAChR expression. In a follow-up proteomics analysis of uterine proteins of rats treated with WF100, a total of 833 proteins was initially detected by LC-MS/MS, with 380 of these proteins commonly detected in all groups of rat uterine tissue samples. A total of 100 proteins were later found to be differentially regulated in rats treated with WF100, with the majority of these proteins showing reduction in their expression levels. When analyzed using STRING, the rat uterine proteins that appeared up-regulated by WF100 displayed six protein-protein interaction networks involving 16 proteins. Whilst many of the protein-protein interaction networks are generally associated with general proteins with structural and regulatory functions, the study also highlighted a network involving Rasrelated C3 botulinum toxin substrate 1 with alpha-actinin-4, which was also shown to interact with transgelin, an actin-crosslinking/gelling protein that may have induced smooth muscle contraction that lead to the abortifacient effects on the rats. When similar STRING analysis was performed on uterine proteins of interest that were down-regulated by WF100, two protein-protein interaction networks were generated involving a total of 56 proteins. One of the networks displayed showed interactions with prostaglandin E synthase 3, which is involved in biosynthesis of this specific type of eicosanoid that inhibits smooth muscle contraction. Hence, this enzyme appeared to have been downregulated so as to induce uterine muscle contraction, inhibit embryo implantation and allow abortion.